2000
DOI: 10.1111/1467-9817.00113
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐assisted learning to read and spell: results from two pilot studies

Abstract: Because multimedia computer programs may provide promising opportunities for the training of initial reading and spelling skills, two small-scale pilot studies have been conducted with a recently-developed program to examine its efficacy and impact on the motivation of the users. The first study is concerned with the use of the program in kindergarten children (K2). As there is no curriculum for these children, a computer program that is fully adaptive may well boost their independence in learning to read and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 13 publications
2
41
0
2
Order By: Relevance
“…Examining the effects of providing an additional literacy instruction resource demonstrated that an adaptable integrated learning system (ILS) program led to higher levels of reading performance for kindergarten children and reduced the level of off-task behavior during instructional times (van Daal & Reitsma, 2000). The data mirrored Foster et al's (1994) findings with the DaisyQuest in early childhood care facilities.…”
Section: Computer As Supplemental Instructionmentioning
confidence: 58%
See 1 more Smart Citation
“…Examining the effects of providing an additional literacy instruction resource demonstrated that an adaptable integrated learning system (ILS) program led to higher levels of reading performance for kindergarten children and reduced the level of off-task behavior during instructional times (van Daal & Reitsma, 2000). The data mirrored Foster et al's (1994) findings with the DaisyQuest in early childhood care facilities.…”
Section: Computer As Supplemental Instructionmentioning
confidence: 58%
“…Where a newer ILS is anticipated to move beyond the previous generation of CAI is in providing additional content and adaptability, overcoming the primary limitations to standard CAI packages. However, positive gains attributed to the ILS are primarily noted only in conditions where there has been ''strong implementation,'' as compared to weak implementations that are characterized by partial or inconsistent use of the materials (van Daal & Reitsma, 2000).…”
Section: Computer As Supplemental Instructionmentioning
confidence: 99%
“…Research has confirmed that by engaging children in enjoyable active learning, what Underwood and Underwood (1998) call edutainment, computerassisted learning promotes language and literacy development (Marsh et al, 2005;Reinking, 1997;Underwood & Underwood, 1998;Valmont, 2000) at the same time that it stimulates motivation to learn. Van Daal and Reitsma (2000) have attributed the positive learning impacts observed among children with low reading motivation and strong feelings of insecurity regarding their learning capacities to the more-structured nature of computer-based learning (when compared to regular classroom instruction), the immediate feedback given by the computer as well as the fact that children using computer technologies become sufficiently involved to remain task-focused for greater lengths of time. With respect to children with special needs, research has indicated that computerized technologies can provide exciting and interesting experiences as well as help improve emergent literacy and writing (Lonigan et al, 2003;Margalit & Roth, 1989;Mioduser, Tur-Kaspa, & Leitner, 2000;Segers, Nooijen, & de Moor, 2006) when programmed to reflect the children's experiences and language (Howell, Erickson, Stanger, & Wheaton, 2000;Hutinger et al, 1998;.…”
Section: Introductionmentioning
confidence: 99%
“…Two pilot studies designed to consider the efficacy of multimedia programmes for the training of reading and spelling are reported by van Daal and Reitsma (2000). In the first study they found that independent computer practice accelerated learning in 5-year olds.…”
Section: Does Ict Facilitate Development?mentioning
confidence: 99%